Antibiotic Prescribing for Pediatric Community-Acquired Pneumonia at Children's Hospitals and General Hospitals Following National Guideline Release. (4th October 2017) - Tribble, Alison; Ross, Rachael; Gerber, Jeffrey S
Abstract: Background: The 2011 IDSA/PIDS guidelines for pediatric community-acquired pneumonia (CAP) recommend penicillin, amoxicillin, or ampicillin (penicillins) as first-line therapy for most children. The use of penicillins increased at children's hospitals after guideline publication, but trends in antibiotic choice for CAP at general hospitals have not been evaluated. Methods: Retrospective analysis of children 1–17 years admitted from January 2009 through September 2015 to 522 hospitals, captured via the Pediatric Health Information System and Premier Perspective databases. Children with CAP were identified by a validated ICD-9 code algorithm, excluding those with complicated pneumonia, complex chronic conditions, receipt of intensive care, or MRSA infection or colonization. Receipt of penicillins, cephalosporins, and macrolides was assessed, and trends were modeled using segmented logistic regression, adjusting for age, sex, and insurance provider. Standardized probability of antibiotic receipt was compared between children's and general hospitals. Results: Of 120, 238 children hospitalized with CAP, 54% were admitted to 51 children's hospitals. After adjustment, penicillin use increased and both cephalosporin and macrolide use decreased in both children's and general hospitals (Figure). However, in the final study year, children in general hospitals were less likely to receive penicillins (standardized probability 0.23, 95% CI [0.17, 0.29] vs. 0.57 [0.52, 0.62]) and more likely to receive cephalosporins (0.78 [0.73, 0.82] vs. 0.51 [0.45, 0.57]) and macrolides (0.43 [0.38, 0.47] vs. 0.28 [0.25, 0.32]) than children in children's hospitals. Conclusion: Publication of national guidelines was associated with improved antibiotic selection for CAP at both children's and general hospitals. However, disparities in prescribing between children's and general hospitals persist. Disclosures: All authors: No reported disclosures.